Οθωμανικός πολιτικός σύνδεσμος και αρμένικο φιλοσυνταγματικό και φιλοδημοκρατικό κόμμα: Ενθοκεντρικά αιτήματα και πολιτικός φιλελευθερισμός - Ανεστίδης, Σταύρος Θ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
The OPL and the ACDP rose within the climate of political excitement engendered by the Young Turks movement of 1908, adopting its ideals and goals. They expoused the fundamental principles of liberty and equality of civic rights and through that prism they sought to promote the political emancipation of the ethnic communities they represent. The cases of these two political formations illustrate the peculiar process of liberalization in Ottoman society, a process which was itself to become stigmatized and undermined by the outbreak of an unbending ethnocentric idealism.